Ubiquitous expression of an activating mutation in the Pik3ca gene reprograms glucose and lipid metabolism in mice. - Sabrina Caiazzo; Matthew J Watt; Garron T Dodd; Jacqueline Bayliss; Helen Thomas; Lorey K Smith; Camilla B Mitchell; Wayne A Phillips (PLoS ONE)
Mutations in PIK3CA, the gene encoding the p110α catalytic subunit of PI3K, are among the most common mutations in human cancers and overgrowth syndromes. The ubiquitous expression of the activating Pik3caH1047R mutation results in reduced survival, organomegaly, hypoglycaemia and hypoinsulinemia in mice. Here we demonstrate that in vivo expression of Pik3caH1047R attenuates the rise in blood glucose in response to oral glucose administration, stimulates glucose uptake in peripheral tissues, inhibits hepatic gluconeogenesis and pancreatic insulin secretion, and increases adipose lipolysis and white adipose tissue browning. Together, our data reveal that the systemic activation of the PI3K pathway in mice disrupts glucose homeostasis through the regulation of hepatic gluconeogenesis, and leads to increased lipolysis of adipose tissue.